Sosialisasi Regulasi dan Kebijakan Kampanye Wali Kota dan Wakil Wali Kota Banjarbaru Tahun 2024 - Anwar Hafidzi; Muhammad Rizky Ramadhan; Lia Nofitasari; Mey Atren Nursasi; Jubaidah; Akhmad Zuhad Haekal (PT. Sharia Journal and Education Center, 2024)
The socialization of campaign policy regulations for mayors and deputy mayors is programmed to provide appeals and explain the rules in campaigning in the elections of mayors and deputy mayors in Banjarbaru city. Kpu as the organizer expects that the socialization of regulations and election campaign policies held will make compliance with the rules reach a high presentation rate. The target of this event consists of various layers of aspects, namely Candidate Pairs, candidate winning teams, political parties, Bawaslu, community organizations, youth organizations and others. The socialization method here uses a face-to-face system in order to get the target of achieving success in socialization.